'It creates a whole linkage with your ancestral line': language socialisation, family lineage, and language choice at diasporic Irish immersion events in Ontario. Issue 3 (16th March 2022) - Giles, Jonathan
ABSTRACT: Colonialism and displacement have not only led to the migration of millions of Irish people and the endangerment of the Irish language, but also to a subjectivity in which it is possible to struggle against the risk of language loss. This paper explores the importance of sharing stories and information about family at second-language Irish immersion events in the diaspora as a cultural behaviour of prime importance that arises out of this subjectivity. These stories are important in the way that they recontextualize family experiences into a diasporic community of practice and because they occur independently of the institutional prerogative to speak Irish at immersion events. Paradoxically, this form of sharing is both foundational to the diasporic Irish-speaking community of practice and poses a challenge to the primacy of Irish as the preferred language of immersion events.